2013
DOI: 10.1002/mds.25276
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum cofactor deficiency presenting with a parkinsonism‐dystonia syndrome

Abstract: voluntarily. Aggressive behaviors, such as biting and shouting, were occasionally observed. Segment 2: At age 32, she was bedridden with generalized rigidity and flexion contractures. She was mute and showed no purposeful movements, although stereotyped arm movements were sometimes observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 5 publications
(1 reference statement)
0
16
0
Order By: Relevance
“…1,6,5 Clinical phenotype is expanding with recognition of lens dislocation as forme fruste of neurologic manifestations, neonatal hyperekplexia with startle and flexor spasms leading to apnea without any electrographic seizure, and adult-onset progressive parkinsonism-dystonia syndrome. 7 The majority of the affected individuals die of the illness within the first few days or weeks of life. 6 Late-onset, milder phenotype with survival into adult life and neurologically asymptomatic patients detected during sibling screening are also reported.…”
mentioning
confidence: 99%
“…1,6,5 Clinical phenotype is expanding with recognition of lens dislocation as forme fruste of neurologic manifestations, neonatal hyperekplexia with startle and flexor spasms leading to apnea without any electrographic seizure, and adult-onset progressive parkinsonism-dystonia syndrome. 7 The majority of the affected individuals die of the illness within the first few days or weeks of life. 6 Late-onset, milder phenotype with survival into adult life and neurologically asymptomatic patients detected during sibling screening are also reported.…”
mentioning
confidence: 99%
“…A late‐onset form has also been reported in literature in 13 patients (Alkufri et al, ; Arenas et al, ; Graf et al, ; Hughes et al, ; Huijmans et al, ; Johnson et al, , ; Mayr et al, ; Megahed et al, ; Mize et al, ; Shih et al, ; Vijayakumar et al, ; Zaki et al, ). Table below compares the clinical, genetic, neurological, and neuroradiological findings of those with our patient.…”
Section: Discussionmentioning
confidence: 78%
“…The classical form manifests in the neonatal period with severe encephalopathy, including intractable seizures, MRI changes that resemble hypoxic‐ischemic injury, microcephaly, and early death (Mechler et al, ). In the literature, an atypical phenotype with late‐onset has been recognized and to date only 13 patients are reported (Alkufri et al, ; Arenas et al, ; Graf, Oleinik, Jack, Weiss, & Johnson, ; Hughes, Fairbanks, Simmonds, & Robinson, ; Huijmans et al, ; Johnson et al, ; Johnson, Wuebbens, Mandell, & Shih, ; Mayr et al, ; Megahed et al, ; Mize, Johnson, & Rajagopalan, ; Shih et al, ; Vijayakumar et al, ; Zaki et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Alkufri et al [6] reported an adult with progressive apathy, slowness of movements, tremor and generalized parkinsonism was reported by and diagnosed as MOCOD.…”
Section: Discussionmentioning
confidence: 99%
“…Patients typically present with neonatal seizure, severe neurodevelopmental delay, epileptic encephalopathy, lens dislocation, feeding difficulties and dysmorphias [3]. Movement disorders have been rarely reported as presenting complaint of MOCOD [4][5][6].…”
Section: Introductionmentioning
confidence: 99%